The physiological aspect of education - Kirk, Clarence Brady (My University, 1906)
Introduction: It is well known that an educated man can not be educated mentally alone but likewise his physical education must receive careful attention. History reveals the fact that for some time past that the physical education of the people has received far too little attention. Today the American people are fast beginning to realize that the mental training is not the only factor in education to be considered. The laws that govern the health and the development of the body are fast taking a place of first importance, because of the relation existing between the mental and physical development. That the two go hand in hand is shown in the individual but here is not the only place. In the history of nations it is found as well. Ancient Greece was the first of nations to make physical exercises a part of its educational exercises. And so long as these practices were exercised the Greek nation rose intellectually and politically and its people became a people of great physical power. Soon riches caused the people to abandon this mode of education and there physical exercises were forgotten in their luxurious living. Then the progress of the nation ceased, her intellectual power soon began to grow less and politically she degenerated fast until the nation fell. Germany has especially in late years made great advancement both intellectually and politically. The Germans themselves attribute a large share of their advancement due to the physical training which has been introduced into the schools and army of that country. England has for many years been among the leading nations in the advancement of the value of physical training in our schools. Here we find many brilliant men, many more than we do in France where no thought is given to the physical side of the education. In our own country where excellence in intellectual ability is being much sought and attained we find that the people are giving much more attention to the physical side of education than a few years ago.
Citation: Kirk, Clarence Brady. The physiological aspect of education. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Education; Physical Education; Theses